Jose "Ka Pepe" W. Diokno makatao, makabayan - Sepeda, Bernardo Noceda (Quezon City C & E Publishing, Inc., 2010)
Life story of Jose W. Diokno, a Filipino human rights activist and nationalist.
"Inilathala ng C & E Publishing, Inc. para sa De La Salle University" on title page verso.
Keywords: Diokno, Jose W; Nationalists -- Philippines -- Biography; Politicians -- Philippines -- Biography; Lawyers -- Philippines -- Biography